ATF5 promotes malignant T cell survival through the PI3K/AKT/mTOR pathway in cutaneous T cell lymphoma - Cao, Mengzhou; Lai, Pan; Liu, Xiangjun; Liu, Fengjie; Qin, Yao; Tu, Ping; Wang, Yang (Frontiers in Immunology, 2023)
Backgrounds: Cutaneous T cell lymphoma (CTCL) is a non-Hodgkin lymphoma characterized by skin infiltration of malignant T cells. The biological overlap between malignant T cells and their normal counterparts has brought obstacles in identifying tumor-specific features and mechanisms, limiting current knowledge of CTCL pathogenesis. Transcriptional dysregulation leading to abnormal gene expression profiles contributes to the initiation, progression and drug resistance of cancer. Therefore, we aimed to identify tumor-specific transcription factor underlying CTCL pathology.Methods: We analyzed and validated the differentially expressed genes (DEGs) in malignant T cells based on single-cell sequencing data. Clinical relevance was evaluated based on progression-free survival and time to next treatment. To determine the functional importance, lentivirus-mediated gene knockdown was conducted in two CTCL cell lines Myla and H9. Cell survival was assessed by examining cell viability, colony-forming ability, in-vivo tumor growth in xenograft models, apoptosis rate and cell-cycle distribution. RNA-sequencing was employed to investigate the underlying mechanisms.Results: Activating transcription factor 5 (ATF5) was overexpressed in malignant T cells and positively correlated with poor treatment responses in CTCL patients. Mechanistically, ATF5 promoted the survival of malignant T cells partially through the PI3K/AKT/mTOR pathway, and imparted resistance to endoplasmic reticulum (ER) stress-induced apoptosis.Conclusions: These findings revealed the tumor-specific overexpression of the transcription factor ATF5 with its underlying mechanisms in promoting tumor survival in CTCL, providing new insight into the understanding of CTCL's pathology.